A study to know the serum total testosterone levels in type II diabetes mellitus male patients from North India - Agarwal, Saurabh; Kumar, Brijesh; ., Sushmita; Giri, Richa; Verma, Sanjay Kumar (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes mellitus is major public health issue facing the world in present century and the prevalence of type 2 diabetes is increasing explosively. There are various diabetes related complications, one of which is low testosterone levels in men. This study was designed to estimate the serum testosterone level in male patients of type 2 diabetes mellitus. Methods: The patients of type -2 diabetes mellitus were picked up from out-patient and in-patients section of the hospital at random. Results: Seventy male patients with type 2 diabetes mellitus were enrolled during the study period. The mean age of study population was 56.36±10.26 years (range 36-70), while that of control group patients was found to be 39.80±7.92years. Family history of diabetes was present in 14 (22.2%) patients. The mean HbA1c in study group was 8.83±1.95 %, which was significantly higher as compared to control group with HbA1c 4.82±0.40 %. Among study group, lower serum total testosterone level was observed in 85.7 % cases and normal level in 14.3 % cases. Among control group, lower serum total testosterone level was observed in 6.7 % cases and normal level in 93.3 % cases. Conclusions: The present study highlighted that significant difference in serum total testosterone level has been observed between cases and control groups (X2 =55.7, P=0.0001).